Comparative Genomics of Strictly Vertically Transmitted, Feminizing Microsporidia Endosymbionts of Amphipod Crustaceans. (20th November 2020) - Cormier, Alexandre; Chebbi, Mohamed Amine; Giraud, Isabelle; Wattier, Rémi; Teixeira, Maria; Gilbert, Clément; Rigaud, Thierry; Cordaux, Richard
Abstract: Microsporidia are obligate intracellular eukaryotic parasites of vertebrates and invertebrates. Microsporidia are usually pathogenic and undergo horizontal transmission or a mix of horizontal and vertical transmission. However, cases of nonpathogenic microsporidia, strictly vertically transmitted from mother to offspring, have been reported in amphipod crustaceans. Some of them further evolved the ability to feminize their nontransmitting male hosts into transmitting females. However, our understanding of the evolution of feminization in microsporidia is hindered by a lack of genomic resources. We report the sequencing and analysis of three strictly vertically transmitted microsporidia species for which feminization induction has been demonstrated ( Nosema granulosis ) or is strongly suspected ( Dictyocoela muelleri and Dictyocoela roeselum ), along with a draft genome assembly of their host Gammarus roeselii . Contrary to horizontally transmitted microsporidia that form environmental spores that can be purified, feminizing microsporidia cannot be easily isolated from their host cells. Therefore, we cosequenced symbiont and host genomic DNA and devised a computational strategy to obtain genome assemblies for the different partners. Genomic comparison with feminizing Wolbachia bacterial endosymbionts of isopod crustaceans indicated independent evolution of feminization in microsporidia and Wolbachia at the molecular genetic level. Feminization thus represents a remarkable evolutionary convergence of eukaryotic and prokaryotic microorganisms. Furthermore, a comparative genomics analysis of microsporidia allowed us to identify several candidate genes for feminization, involving functions such as DNA binding and membrane fusion. The genomic resources we generated contribute to establish Gammarus roeselii and its microsporidia symbionts as a new model to study the evolution of symbiont-mediated feminization.